Random-access accelerator (RAA): A framework to Speed up the random-access procedure in 5G new radio for IoT mMTC by enabling device-to-device communications - Medel, Abel Rodriguez (2020)
Mobile networks have a great challenge by serving the expected billions of Internet of Things (IoT) devices in the upcoming years. Due to the limited simultaneous access in the mobile networks, the devices should compete one another for resource allocation during a Random-Access procedure. This contention provokes a non-depreciable delay during the devices??? registration because of the great number of collisions experienced. To overcome such a problem, a framework called Random-Access Accelerator (RAA) is proposed in this work, in order to speed up network access in massive Machine Type Communication (mMTC). RAA exploits Device-To-Device (D2D) communications, where devices with already assigned resources act like relays for the rest of devices trying to gain access in the network. The simulation results show an acceleration in the registration procedure of 99%, and a freed space of the allocated spectrum until 68% in comparison with the conventional Random-Access procedure. Besides, it preserves almost the same devices??? energy consumption compared with legacy networks by using Bluetooth Low Energy (BLE) as the wireless technology for D2D communications. The proposed framework can be taken into account for the standardization of mMTC in Fifth-Generation-New Radio (5G NR).